Concentration quenching mechanism of dysprosium(III) ions in silicate-substituted fluorapatite - Targońska, Sara; Wiglusz, Rafal J. (Ceramics international, 2023)
Silicon-substituted apatite doped with Dy3+ ions was obtained by using microwave assisted hydrothermal techniques. The general formula of obtained samples is related to Ca10-xDyx(PO4)2(SiO4)4F2, where x = 0.05; 0.1; 0.2; 0.5. The structural, and morphological features of the obtained materials were determined by using XRD (X-ray powder diffraction) and SEM imaging (Scanning Electron Microscopy). The Rietveld refitment was used for estimation of unit-cell parameters. The photoluminescence of the Dy3+ ions was detected and analysed as a function of dopant concentration. The particular attention was focused on the concentration quenching of Dy3+ ion luminescence as well as the critical transfer radius was calculated. The chromaticity diagram, emission colour and correlated colour temperature (CCT) were evaluated.